(untitled) (AYUSHDHARA, 2017)
Introduction: Butea monosperma, a deciduous tree belonging to the family Faboideae, is found growing in many parts of India. All the parts of plant are highly medicinal with its mention in different systems of medicine. Several review works have summarized the potential efficiency of this plant. Objective: The present work attempts to evaluate the physicochemical and preliminary phytochemical studies on the flowers of Butea monosperma Koen. Ex Roxb, family Fabaceae. The work is done for pharmacognostic standardization and authentication of flowers of Butea monosperma. Methods: The herbal standardization was carried out on the basis of organoleptic properties, physical characteristics, and physico-chemical properties. Physicochemical parameters including ash values, extractive values, loss on drying, foreign matter were evaluated. Results: Powder is yellowish brown, velvety in texture, bitter in taste and smells chocolaty. The Loss on Drying at 105 c, total ash and acid insoluble ash were found to be 5.39%, 7.82%, 1.07%, w/w respectively. Ethanol and water soluble extractive values (hot)were 14.21%, 22%w/w respectively. The extracts were subjected to preliminary phytochemical screening and the results certified the presence of alkaloids, phenols, flavonoids, triterpinoids, steroids, carbohydrates, proteins and saponins in alcohol and aqueous extracts of flower. Conclusion: These studies provided referential information for correct identification and standardization of this plant material.